Dose Remittances Matter for Openness and Financial Stability: Evidence From Least Developed Economies - Miao, Meng; Qamruzzaman, Md. (Frontiers in Psychology, 2021)
The study's motivation is to gauge the effects of remittances on openness: financial and economic openness and financial stability in the least developed countries for the period spanning from 1976-2018. The study applies Generalized Moment of Methods (GMM) and System-GMM for detecting the magnitude of remittances, capital formation, and government debt on openness and financial stability and their directional association establishes by performing a granger causality test with System-GMM specification. Panel cointegration test based on error correction confirms the availability of long-run association among variables. In LDCs, remittances inflow positively augmented economic and financial openness; moreover, bringing financial stability remittances plays a critical role. The feedback hypothesis explains the causal effects of openness and remittances and financial stability and remittances with consideration of directional causality.